Exploiting the linked teaching and learning international survey and programme for international student assessment data in examining school effects: A case study of Singapore - Liu, Xin; Valcke, Martin; Yang Hansen, Kajsa; De Neve, Jan (Frontiers in Education, 2022)
This paper attempts to demonstrate the usefulness of the linkage data from two international large-scale assessment studies, TALIS 2013 and PISA 2012, in examining the effects of schools. Data from seven educational systems are used to link, and four critical issues with five selection criteria are applied to the data selected. The linking dataset facilitates the investigation of mathematics performance while considering individual learner characteristics, mathematics teacher variables in the classroom environment and the school-level variables. We extend the new avenue of research by developing a linked database geared to the specific mathematics teaching and learning domain to reflect the school mathematics educational environment. The case study using Singapore linkage data demonstrated the feasibility and potential of exploring school effectiveness. In Singapore, schools with teachers of a higher level of education and self-efficacy in teaching mathematics related to a higher level of school mathematics performance. The study offers a guideline and inspiration to the research community to exploit the rich information in both TALIS and PISA studies to facilitate school effectiveness studies.